Airway space changes after maxillomandibular counterclockwise rotation and mandibular advancement with TMJ Concepts® total joint prostheses: Three-dimensional assessment - Gonçalves, João Roberto [UNESP]; Gomes, L. C R [UNESP]; Vianna, A. P. [UNESP]; Rodrigues, D. B.; Gonçalves, Daniela Aparecida de Godoi [UNESP]; Wolford, L. M. (Elsevier, 2013)
This study focused on three-dimensional (3D) airway space changes and stability following simultaneous maxillomandibular counterclockwise rotation, mandibular advancement, and temporomandibular joint (TMJ) reconstruction with custom-made total joint prostheses (TMJ Concepts®). Cone beam computed tomography (CBCT) scans of 30 consecutive female patients with irreversibly compromised TMJs were obtained at the following intervals: T1, presurgery; T2, immediately after surgery; and T3, at least 6 months after surgery. The CBCT volumetric datasets were analysed with Dolphin Imaging ® software to evaluate surgical and postsurgical changes to oropharyngeal airway parameters. The average changes in airway surface area (SA), volume (VOL), and minimum axial area (MAA) were, 179.50 mm2, 6302.60 mm3, and 92.23 mm2, respectively, at the longest follow-up (T3 - T1) (P ≤ 0.001). Significant correlations between the amount of mandibular advancement and counterclockwise rotation of the occlusal plane and 3D airway changes were also found (P ≤ 0.01). The results of this investigation showed a significant immediate 3D airway space increase after maxillomandibular counterclockwise rotation and mandibular advancement with TMJ Concepts total joint prostheses, which remained stable over the follow-up period. © 2013 International Association of Oral and Maxillofacial Surgeons.
Keywords: airway remodeling; orthognathic surgery; three-dimensional image; TMJ prostheses; adolescent; adult; aged; clinical article; cone beam computed tomography; correlation analysis; female; follow up; human; mandible reconstruction; oropharynx airway; retrospective study; rotation; surgical patient; temporomandibular joint; three dimensional imaging; total temporomandibular joint prosthesis